2001
DOI: 10.1097/00005537-200108000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy With Picibanil (OK‐432) for Congenital Lymphatic Malformation in the Head and Neck

Abstract: Given with our experience and the reports that failure of picibanil sclerotherapy does not hinder subsequent surgical salvage procedures, we recommend trying picibanil sclerotherapy as a primary treatment for the LMHN and performing surgical excision as a secondary modality if the response to the sclerotherapy is not satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 8 publications
3
64
0
8
Order By: Relevance
“…Previous reports have stated that surgical 86 Motz et al, OK432 Versus Doxycycline for Lymphatic Malformations excision is not more complicated after OK432 sclerotherapy. 2,3,[22][23][24]27,28 We found this to be true in the excision of an organized hematoma.…”
mentioning
confidence: 68%
“…Previous reports have stated that surgical 86 Motz et al, OK432 Versus Doxycycline for Lymphatic Malformations excision is not more complicated after OK432 sclerotherapy. 2,3,[22][23][24]27,28 We found this to be true in the excision of an organized hematoma.…”
mentioning
confidence: 68%
“…104 Sclerotherapy is typically ineffective in treating microcystic LMs, although positive treatment outcomes have been reported with doxycycline, 105 bleomycin 91 and OK-432. 106 In addition, an intermediate response in 50% of cases has also been observed. 94 Thus, sclerotherapy may provide benefit to patients with symptomatic and/or large microcystic LMs.…”
Section: Lymphatic Malformationsmentioning
confidence: 98%
“…The regimen is an effective treatment for unresectable lesions, incomplete resection and recurrent lymphatic malformations (Ogita et al 1991(Ogita et al , 1994Mikhail et al 1995). Some authors considered sclerotherapy with OK-432 to be the initial treatment for lymphatic malformations (Ogita et al 1994;Luzzatto et al 2000;Sung et al 2001). 92%-100% of patients with macrocystic lesions and 41-60% of patients with microcystic lesions have a favorable response (Ogita et al 1994;Luzzatto et al 2000;Sanlialp et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ogita et al (1987Ogita et al ( , 1991Ogita et al ( , 1994 also suggested that the local inflammation caused by OK-432 did not cause any damage to the overlying skin and did not lead to scar formation. However, transient facial nerve palsy after sclerotherapy with OK-432 at the parotid area has previously been reported, and believed that stretching of the nerve by swelling was regarded as the principal cause (Sung et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation